TAYANGAN PROGRAM LUDRUK BANYOLAN KARTOLO DI JTV SURABAYA - Mega Pandan Wangi (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2013)
The directing of the program Ludruk Banyolan Kartolo (LBK) is carried out and influenced by elements of production, and itsaesthetic is formed in such a way that the LBK program can be packaged and broadcast in a way that is appropriate and canalso be enjoyed by the television audience. The directing of LBK is influenced by production elements such as the synopsis,program director, floor director, production assistant, camera operator, sound engineer, lighting engineer, and artistic arranger.The directing of this program can also be viewed from two strategies, namely the visual strategy, which is influenced by thecharacterization, dramatic plot, and the way in which the dramatic plot is created, and the media strategy, which is influencedby the techniques used for taking pictures and editing. The result of the LBK program, which is analysed and studied from theperspective of AAM Djelantik’s aesthetics, and viewed from the point of view of its form, quality, and appearance, shows thatthe properties used are still inadequate since the situation and conditions of every segment are the same. In addition, theuniformity of materials, costumes, and properties must also be addressed in order to improve the packaging and result of theshow.Keywords: show, program, Ludruk Banyolan Kartolo